Management : leading & collaborating in a competitive world - Bateman, Thomas S.; Snell, Scott (New York, NY, USA : McGraw-Hill Education, 2015)
Includes four traditional functions of planning, organizing, leading, and controlling, while modernizing and re-visioning the concepts as delivering strategic value, building a dynamic organization, mobilizing people, and learning and changing.
PART ONE: Foundations of Management Chapter 1: Managing and Performing Chapter 2: The External and Internal Environments Chapter 3: Managerial Decision Making PART TWO: Planning: Delivering Strategic Value Chapter 4: Planning and Strategic Management Chapter 5: Ethics, Corporate Responsibility, and Sustainability Chapter 6: International Management Chapter 7: Entrepreneurship PART THREE: Organizing: Building a Dynamic Organization Chapter 8: Organization Structure Chapter 9: Organizational Agility Chapter 10: Human Resources Management Chapter 11: Managing the Diverse Workforce PART FOUR: Leading: Mobilizing People Chapter 12: Leadership Chapter 13: Motivating for Performance Chapter 14: Teamwork Chapter 15: Communicating CHAPTER FIVE: Controlling: Learning and Changing Chapter 16: Managerial Control Chapter 17: Managing Technology and Innovation Chapter 18: Creating and Leading Change
"This International Student edition is for use outside the U.S."--Cover.
Keywords: Management